Sethusamudram Shipping Canal Project : in need of divine intervention - Chandrasekaran, K.; Bhardwaj, Sachin; Raghuram, G. (London : SAGE Publications Ltd, 2017)
It was January 21, 2012, a cold and foggy day in Delhi. As Rajendra Pachauri stepped out of the meeting, he knew this was going to be harder than he had imagined. Three and a half years earlier, in July 2008, Dr Manmohan Singh, the Prime Minister of India, had appointed Pachauri as the head of a six-member committee to examine an alternative alignment (Alignment 4A) for the controversial Sethusamudram Shipping Canal Project (SSCP) and provide its recommendations as soon as possible.
Originally published: Chandrasekaran, K., Bhardwaj, S. & Raghuram, C. 2014. Sethusamudram shipping canal Project: In need of divine intervention. CIPR0016. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Pachauri, Rajendra; Sethusamudram Shipping Canal Project (SSCP); Water resources development -- India -- Delhi; Community development -- India -- Delhi